2020
DOI: 10.1186/s12877-020-01508-9
|View full text |Cite
|
Sign up to set email alerts
|

AMPI-AB validity and reliability: a multidimensional tool in resource-limited primary care settings

Abstract: Background: The early identification of individuals at high risk for adverse outcomes by a Comprehensive Geriatric Assessment (CGA) in resource-limited primary care settings enables tailored treatments, however, the evidence concerning its benefits are still controversial. The main objective of this study was to examine the validity and reliability of the "Multidimensional Assessment of Older People in Primary Care (AMPI-AB)", a CGA for primary care in resource-limited settings. Methods: Longitudinal study, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
3
0
5
Order By: Relevance
“…Considerando os componentes do fenótipo de fragilidade proposto por Fried et al (2001), quanto a comportamento sedentário, fraqueza e diminuição da marcha (2001) também é utilizado para subsidiar a validade de outras propostas de assistência à saúde para pessoas idosas na condição de fragilidade, a exemplificar a AMPI-AB, desenvolvida por especialistas em geriatria, gerontologia e saúde pública da Secretaria Municipal de Saúde de São Paulo (SÃO PAULO, 2021). O instrumento está em processo de validação, e estudos preliminares demostraram boa acurácia e confiabilidade na gestão de saúde de idosos (ANDRADE et al, 2020;SARAIVA et al, 2020).…”
Section: Discussionunclassified
“…Considerando os componentes do fenótipo de fragilidade proposto por Fried et al (2001), quanto a comportamento sedentário, fraqueza e diminuição da marcha (2001) também é utilizado para subsidiar a validade de outras propostas de assistência à saúde para pessoas idosas na condição de fragilidade, a exemplificar a AMPI-AB, desenvolvida por especialistas em geriatria, gerontologia e saúde pública da Secretaria Municipal de Saúde de São Paulo (SÃO PAULO, 2021). O instrumento está em processo de validação, e estudos preliminares demostraram boa acurácia e confiabilidade na gestão de saúde de idosos (ANDRADE et al, 2020;SARAIVA et al, 2020).…”
Section: Discussionunclassified
“…Some quick and easy-to-use CGA-based tools have been validated to facilitate the use of geriatric measures in practice. 3,12,94 These tools are less time-consuming and do not require skilled resources, which are challenging to obtain in most clinical settings. For example, the 10-TaGA offers information on ten health domains using a practical method that combines self-reported items and performance tests.…”
Section: Barriers and Future Perspectivesmentioning
confidence: 99%
“…7 Previous studies have demonstrated the importance of comprehensive geriatric assessment (CGA) in guiding the care of older people. [10][11][12][13] It complements the conventional medical approach by integrating information on social, physical, cognitive, and psychological aspects related to function and interferes progressively with health and quality of life as people age. 3,14 CGA was conceived by Dr. Marjory Warren during a successful interdisciplinary rehabilitation initiative offered to in-hospital patients with disabilities in London during the first half of the 20th century.…”
Section: Introductionmentioning
confidence: 99%
“…Recentemente foi publicado artigo examinando a validade e a confiabilidade do instrumento AMPI-AB, onde a mesma foi considerada instrumento válido e confiável para avaliar idosos em ambiente de atenção primária com recursos escassos. Sendo precisa na detecção de fragilidade física e prévia de mortalidade, agravo de incapacidades, hospitalizações, consultas de emergência e quedas entre os idosos na atenção primária (Saraiva et al, 2020). Trata-se do primeiro estudo que avalia um instrumento para gerenciar cuidados de saúde de idosos em um sistema de saúde pública em países de média-baixa renda, foi desenvolvido por um conjunto de especialistas em saúde pública, geriatria e gerontologia.…”
Section: Tipo De Estudo E Aspectos éTicosunclassified